2020
DOI: 10.3390/ph13110358
|View full text |Cite
|
Sign up to set email alerts
|

Masked Phenolic-Selenium Conjugates: Potent and Selective Antiproliferative Agents Overcoming P-gp Resistance

Abstract: Cancer accounts for one of the most complex diseases nowadays due to its multifactorial nature. Despite the vast number of cytotoxic agents developed so far, good therapeutic approaches are not always reached. In recent years, multitarget drugs are gaining great attention against multifactorial diseases in contraposition to polypharmacy. Herein we have accomplished the conjugation of phenolic derivatives with an ample number of organochalcogen motifs with the aim of developing novel antiproliferative agents. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 72 publications
0
9
0
Order By: Relevance
“…5-Bromo-2-chloro-6-methylpyrimidine-4-selenolate is produced through the reduction reaction of selenocyanatopyrimidine (2) with sodium borohydride at the temperature of 0-5 C in methanol, followed by the nucleophilic substitution reaction with various alkyl halides for 30 min [47][48][49]. The corresponding heterocyclic alkyl selenides (3a-e) were prepared in 86%-90% yields.…”
Section: Resultsmentioning
confidence: 99%
“…5-Bromo-2-chloro-6-methylpyrimidine-4-selenolate is produced through the reduction reaction of selenocyanatopyrimidine (2) with sodium borohydride at the temperature of 0-5 C in methanol, followed by the nucleophilic substitution reaction with various alkyl halides for 30 min [47][48][49]. The corresponding heterocyclic alkyl selenides (3a-e) were prepared in 86%-90% yields.…”
Section: Resultsmentioning
confidence: 99%
“…It was also observed that, even though the toxicity toward the healthy cells was slightly raised, the potency of one of the selenoderivatives reported was enhanced up to 30-fold, thus increasing the overall SI. 254 In summary, even though in most cases, Se incorporation may enhance the toxicity of a molecule toward normal cells, it can also more significantly increase the toxicity toward cancer cells, thus increasing the overall TI. The lower dose requirements to achieve a similar or better efficacy as compared to the parent compounds could thus also ensure better target selectivity for a Se containing small molecule.…”
Section: Discussionmentioning
confidence: 99%
“…5-(selenocyanatomethyl)benzo[d][ 1 , 3 ]dioxole ( 10b ) [ 52 ] was purified by silica gel chromatography column (hexanes/AcOEt = 9/1) to afford a yellow solid, 97.2 mg (81% yield); m.p. = 70.0–71.5 °C; 1 H NMR (CDCl 3 , 400 MHz) δ = 6.82–6.81 (m, 2H), 6.77–6.75 (m, 1H), 5.96 (s, 2H), 4.23 (s, 2H).…”
Section: Methodsmentioning
confidence: 99%